Activated CAMKKβ-AMPK signaling promotes autophagy in a spheroid model of ovarian tumour metastasis - Jeremi Laski; Bipradeb Singha; Xu Wang; Yudith Ramos Valdés; Olga Collins; Trevor G. Shepherd (BMC, 2020)
Abstract Background A hallmark of epithelial ovarian cancer (EOC) metastasis is the process of spheroid formation, whereby tumour cells aggregate into 3D structures while in suspension in the peritoneal cavity. EOC spheroids are subjected to bioenergetic stress, thereby activating AMP-activated protein kinase (AMPK) signaling to enter a metabolically quiescent state, which can facilitate cell survival under nutrient-limiting conditions. Independently, we have also demonstrated that EOC spheroids induce autophagy, a process that degrades and recycles intracellular components to restore energy and metabolites. Herein, we sought to examine whether AMPK controls autophagy induction as a cell survival mechanism in EOC spheroids. Results We observed a co-ordinate increase in phosphorylated AMPK and the autophagy marker LC3-II during EOC spheroid formation. Reduced AMPK expression by siRNA-mediated knockdown of PRKAA1 and PRKAA2 blocked autophagic flux in EOC spheroids as visualized by fluorescence microscopy using the mCherry-eGFP-LC3B reporter. A complementary approach using pharmacologic agents Compound C and CAMKKβ inhibitor STO-609 to inhibit AMPK activity both yielded a potent blockade of autophagic flux as well. However, direct activation of AMPK in EOC cells using oligomycin and metformin was insufficient to induce autophagy. STO-609 treatment of EOC spheroids resulted in reduced viability in 7 out of 9 cell lines, but with no observed effect in non-malignant FT190 cell spheroids. Conclusions Our results support the premise that CAMKKβ-mediated AMPK activity is required, at least in part, to regulate autophagy induction in EOC spheroids and support cell viability in this in vitro model of EOC metastasis.